Special education in the Sultanate of Oman - Nasser Hinai, Musaab Salim; Amzat, Ismail Hussein; Abdul Hamid, Siti Rafiah (AHAS KIRKHS, IIUM, 2025)
The study aimed to identify the current state of the special education system in the Sultanate of Oman and its role in supporting individuals with special needs. It also sought to propose a strategy for the development of the special education system in the Sultanate. The study employed the descriptive-analytical method due to its suitability for the nature of the research. The study concluded with a proposed strategy for the development of the special education system in the Sultanate of Oman.